Effects of low emission zones and congestion charging zones on physical health outcomes: a systematic review. - Chamberlain,RC; Fecht,D; Davies,B; Laverty,AA (2022)
BACKGROUND: Road traffic impacts human health through air pollution and road safety issues. Low emission zones (LEZs) and congestion charging zones (CCZs) have therefore been implemented in several cities globally. We systematically reviewed the evidence on the effects of these pollution or congestion reduction schemes on specific physical health outcomes associated with air pollution or traffic exposure. METHODS: We searched MEDLINE, Embase, Web of Science, IDEAS, Greenfile, and TRID databases from database inception to Feb 22, 2022, using search terms such as "low emission/congestion charge/zone" and "cardiovascular/respiratory/injury". Searches were limited to English-language records. We included studies that evaluated the effect of a LEZ or CCZ on air pollution-related outcomes (ie, cardiovascular disease, respiratory disease, birth outcomes, dementia, lung cancer, diabetes) or road traffic injuries, using longitudinal study designs. We excluded studies without empirical health data. Two authors independently assessed papers for inclusion. Results were narratively synthesised and summarised using harvest plots. Risk of bias was assessed using the Graphic Appraisal Tool for Epidemiological studies for correlation studies. This systematic review was registered with PROSPERO, number CRD42022311453. FINDINGS: Of 2068 post-deduplication records screened, fifteen studies were included, with two further studies included from references of eligible studies. Nine (53%) of 17 studies assessed LEZs in London, Milan, Tokyo, and several German cities, seven (41%) assessed the London CCZ, and one (6%) assessed the Stockholm CCZ. Each predefined health outcome was considered by at least one study. Six (75%) of eight LEZ studies considering pollution-related outcomes identified reductions in at least one outcome, with all five on cardiovascular disease identifying reductions for at least one disease subcategory. Of seven London CCZ studies, six (86%) report